EFFECT OF PENICILLIUM SPECIES ON THE ANTIBIOTIC RESISTANCE PROFILE OF ALCALIGENES FAECALIS - Alkhalil, Samia S. (African Journal of Infectious Diseases (AJID), 2024)
Background: Infectious diseases due to antibiotic resistant pathogens are a global public health problem, with the impact been particularly pronounced in sub-Saharan Africa. This study aimed at determining the potential effect of bacterial–fungal interaction on the antibiotic susceptibility profile of Alcaligenes faecalis. Materials and Method: Alcaligenes faecalis was isolated from water samples. The isolate was identified using the conventional biochemical tests and the 16S rRNA molecular sequencing technique. Additionally, Penicillium species was isolated and identified based on colony morphological characteristics and microscopic features. Standardized isolates were co-cultured cultured in broth medium. Antibiotic susceptibility evaluation of the Alcaligenes faecalis from the co-culture and the original Alcaligenes faecalis was carried out using the Kirby bauer disk diffusion method. Results: The antibiotic susceptibility profile of Alcaligenes faecalis before and after co-culture remained largely unchanged except in the case of chloramphenicol, were the isolate showed reduced susceptibility. Molecular analysis of resistance gene revealed the absence of tested gene encoding antibiotic resistance, including the streptomycin resistance (str) genes (STRA and STRB) and the erythromycin resistance methylase (ERM) gene. Conclusion: Further research involving a wide spectrum of microorganisms and their interactions should be conducted to acquire a thorough understanding of the influence of microbial interactions on antibiotic susceptibility profiles in order to pave way for novel strategies to combat antimicrobial resistance.